SKREENING FITOKIMIA DAUN SEGAR Nypa fruticans Wurmb ASAL PESISIR ACEH BARAT - Mohamad Gazali; Hayatun Nufus (Universitas Teuku Umar, 2019)
West Aceh Region have Nypa fruticans mangrove community that distributed almost ± 100 Ha. But there are several habitat of N. fruticans have experienced damage that caused by tsunami. The utilization of N. fruticans still limited that only utilized its leaves as cigarette. The utilization of N. fruticans toward marine natural product for overcoming healthy community. The aim of this research is to study the phytochemical screening of N. fruticans fresh leave from the coast of West Aceh. The method was used by using experimental. The result shown phytochemical properties in N. fruticans fresh leaves shown that N. fruticans plant contained phenolic, flavonoid, tannin, saponin and triterpenoid. This indicated that the phenolic, flavonoid, tannin and saponin compounds in such sample that have potency as food and non-food sources. Keywords : Phytochemical, West Aceh, Screening, N. fruticans leaveWest Aceh Region have Nypa fruticans mangrove community that distributed almost ± 100 Ha. But there are several habitat of N. fruticans have experienced damage that caused by tsunami. The utilization of N. fruticans still limited that only utilized its leaves as cigarette. The utilization of N. fruticans toward marine natural product for overcoming healthy community. The aim of this research is to study the phytochemical screening of N. fruticans fresh leave from the coast of West Aceh. The method was used by using experimental. The result shown phytochemical properties in N. fruticans fresh leaves shown that N. fruticans plant contained phenolic, flavonoid, tannin, saponin and triterpenoid. This indicated that the phenolic, flavonoid, tannin and saponin compounds in such sample that have potency as food and non-food sources. Keywords : Phytochemical, West Aceh, Screening, N. fruticans leave